A arte de pintar - Lopes , Cleuza Francisca da Silva; Oliveira, Maria de Fátima; Lima , Maria dos Santos; Simião, Regina Aparecida Versoza; Guimarães , Renata Maria de Souza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf